High-temperature-resistant ceramic formula and preparation process thereof
By adding composite thermal conductive materials and reinforcement fibers to the ceramic material to form a mesh structure, the problems of existing ceramic materials being prone to breakage and coating powder at high temperatures are solved, and the high wear and high temperature resistance of ceramic materials are achieved.
Patent Information
- Application Number
- CN202411889808.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing ceramic materials are prone to brittle fracture when they are subjected to impact or vibration loads, and the firing structure and mass change at high temperatures, resulting in coating powdering, poor wear and high temperature resistance.
A high-temperature resistant ceramic formula is adopted, including ceramic blast materials, glaze materials, composite thermal conductivity materials and reinforcement fibers. The composite thermal conductivity materials and reinforcement fibers are mixed in the ceramic blast body and glaze materials. By strictly controlling the proportion of each component and the preparation process parameters, a network structure is formed to improve the strength and thermal conductivity of the ceramic.
It significantly improves the wear and high temperature resistance of ceramic materials, enhances its strength, reduces the occurrence of cracks, and improves thermal conductivity to prevent coating powdering.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic formulations, and in particular to a high-temperature resistant ceramic formulation and a preparation process thereof. Background Art
[0002] Ceramics are materials and products made from clay as the main raw material and various natural minerals through crushing, mixing, molding and calcining. People call objects made of a kind of clay and fired at high temperature in a special kiln ceramics. Ceramics is a general term for pottery and porcelain. Among them, daily-use ceramics are a variety of ceramic products and the oldest and most commonly used traditional ceramics. This type of ceramic product has the widest practicality and appreciation. It can increase the stability and dielectric strength of the object and prevent the erosion of liquids and gases. It is not only beautiful and easy to wash, but also not stained by dust.
[0003] Existing ceramics have poor strength and are prone to brittle fracture when subjected to impact or vibration loads. When the operating temperature is too high, it will cause changes in the structure and quality of the fired ceramics, resulting in powdering of the coating, resulting in unsatisfactory performance in terms of wear resistance and high temperature resistance. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a high temperature resistant ceramic formula and a preparation process thereof to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a high temperature resistant ceramic formula, comprising the following raw materials: Ceramic blank, glaze, composite thermal conductive material and reinforcing fiber, wherein the composite thermal conductive material and reinforcing fiber are mixed inside the ceramic blank and the glaze; The specific formula includes the following raw materials: the mass ratio of the composite thermal conductive material, the reinforcing fiber and the ceramic body is (2-3): (6-8): 100, and the mass ratio of the composite thermal conductive material, the reinforcing fiber and the glaze is (3-4): (7-9): 100.
[0006] Preferably, the high temperature resistant ceramic formula comprises the following raw materials: The mass ratio of the composite thermal conductive material, the reinforcing fiber and the ceramic body is 2.5:7:100, and the mass ratio of the composite thermal conductive material, the reinforcing fiber and the glaze is 3.5:8:100.
[0007] Preferably, the ceramic blank comprises the following raw materials: 30-40 parts of clay, 10-12 parts of alkaline earth, 15-18 parts of refractory clay, 3-5 parts of mullite powder, and 10-13 parts of titanium oxide; The glaze comprises the following raw materials: 15-20 parts of potassium feldspar, 10-12 parts of aluminum ore, 10-12 parts of quartz sand, 12-15 parts of kaolin, 8-15 parts of spodumene, 8-10 parts of calcite, 3-5 parts of black jade, 12-15 parts of calcium phosphate, 6-8 parts of nano titanium dioxide, 8-10 parts of basic magnesium carbonate and 2-5 parts of boric acid.
[0008] Preferably, the reinforcing fibers include quartz ceramic fibers and silicon carbide ceramic fibers in a 1:1 ratio, the quartz ceramic fibers have a diameter of 3-8 μm and a length of 0.1-0.3 mm, and the silicon carbide ceramic fibers have a diameter of 4-6 μm and a length of 0.1-0.2 mm.
[0009] Preferably, the method for preparing the composite thermal conductive material comprises the following steps: S1, after natural graphite is rolled, a natural graphite strip with a thickness of 0.5-1.0 mm and a density greater than or equal to 1 g / ml is obtained, and then put into a pulverizer for the first pulverization process to obtain medium and low density graphene powder; S2, the obtained low and medium density graphene powder is molded into blocks to obtain a graphite block with a density greater than or equal to 2g / ml, and then put into a pulverizer for secondary pulverization to obtain a high-density graphene powder; S3. Evenly mix the high-density graphene powder and alumina powder, put them into a vacuum sintering furnace, heat them to high temperature for sintering, and then put them into a pulverizer for three pulverizations after cooling to obtain a composite thermal conductive material.
[0010] Preferably, the sintering temperature in the vacuum sintering furnace is 500-800° C., and the sintering time is 1-2 hours.
[0011] Preferably, the composite thermal conductive material is placed in a grinder and fully ground so that the material can pass through a 200-300 mesh screen.
[0012] The present invention also provides a preparation process of high temperature resistant ceramics, comprising the following steps: Step 1: grind, wash and remove impurities from the ceramic blank and mix them evenly, then add the composite thermal conductive material and reinforcing fiber and mix them into a slurry for making ceramics, pour the mixed slurry into a mold with microporous holes, let it stand, drain the water by vacuum filtration, and press to obtain a ceramic wet blank; Step 2: Place the formed wet ceramic embryo in a vacuum drying oven for 3-5 hours, and then place it on a wooden rack for air drying, so that the moisture content of the ceramic embryo is controlled at 7-9%, thereby obtaining a dry ceramic embryo; Step 3: Select and remove impurities from the glaze, grind it into powder in a ball mill according to the glaze ratio, then add water, composite thermal conductive material and reinforcing fiber and mix for 1-2 hours, and adjust the glaze concentration to obtain glaze slurry; Step 4: spray the glaze slurry on the surface of the ceramic dry blank, and then put it into a calcining furnace for calcination. The calcination temperature is 1150-1250°C. After calcination for 10-12 hours, keep warm for 3-5 hours. After calcination, cool it to obtain a high-temperature resistant ceramic.
[0013] Preferably, the ball milling time of the glaze is 20-25 hours, and the fineness after ball milling is through a 200-250 mesh sieve.
[0014] Preferably, programmed cooling is used during the cooling, specifically, the temperature is reduced to 1000° C. in 60 minutes, kept at that temperature for 50 minutes, then reduced to 500° C. in 60 minutes, kept at that temperature for 30 minutes, and then reduced to room temperature in 40 minutes.
[0015] The high temperature resistant ceramic formula and preparation process thereof prepared by the present invention strictly control the proportion of each component of the ceramic blank and glaze and the preparation process parameters, and add reinforcing fibers to the ceramic blank and glaze. Because the reinforcing fibers are thin and soft, they will naturally bend during stirring and molding, which will not affect the use, thereby increasing the strength of the ceramic and reducing cracks. At the same time, a composite thermal conductive material is added, wherein the graphite powder and alumina powder can be evenly distributed in the ceramic blank and glaze, and form a network structure with the reinforcing fibers. The thermal conductivity of the graphite powder greatly improves the thermal conductivity of the ceramic material, effectively disperses the load, disperses the stress, and prevents the crack from expanding. At the same time, the alumina powder can promote the burning of the material because of its relatively small particles, large surface area, and good activity, so that the ceramic has better wear resistance and high temperature resistance. DETAILED DESCRIPTION
[0016] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] The present invention of this embodiment provides a high temperature resistant ceramic formula, comprising the following raw materials: ceramic blank, glaze, composite thermal conductive material and reinforcing fiber, wherein the composite thermal conductive material and reinforcing fiber are mixed inside the ceramic blank and glaze; The specific formula includes the following raw materials (by mass): the mass ratio of the composite thermal conductive material, the reinforcing fiber and the ceramic body is (2-3): (6-8): 100, and the mass ratio of the composite thermal conductive material, the reinforcing fiber and the glaze is (3-4): (7-9): 100.
[0018] The high temperature resistant ceramic formula of this embodiment includes the following raw materials: The mass ratio of the composite thermal conductive material, the reinforcing fiber and the ceramic body is 2.5:7:100, and the mass ratio of the composite thermal conductive material, the reinforcing fiber and the glaze is 3.5:8:100.
[0019] The ceramic blank of this embodiment includes the following raw materials (by mass): 30-40 parts of clay, 10-12 parts of alkaline earth, 15-18 parts of refractory clay, 3-5 parts of mullite powder, and 10-13 parts of titanium oxide; The glaze includes the following raw materials (by mass): 15-20 parts of potassium feldspar, 10-12 parts of aluminum ore, 10-12 parts of quartz sand, 12-15 parts of kaolin, 8-15 parts of spodumene, 8-10 parts of calcite, 3-5 parts of black jade, 12-15 parts of calcium phosphate, 6-8 parts of nano titanium dioxide, 8-10 parts of basic magnesium carbonate, and 2-5 parts of boric acid.
[0020] The reinforcing fibers of this embodiment include quartz ceramic fibers and silicon carbide ceramic fibers in a ratio of 1:1. The quartz ceramic fibers have a diameter of 3-8 μm and a length of 0.1-0.3 mm, and the silicon carbide ceramic fibers have a diameter of 4-6 μm and a length of 0.1-0.2 mm.
[0021] The preparation method of the composite thermal conductive material of this embodiment comprises the following steps: S1, after natural graphite is rolled, a natural graphite strip with a thickness of 0.5-1.0 mm and a density greater than or equal to 1 g / ml is obtained, and then put into a pulverizer for the first pulverization process to obtain medium and low density graphene powder; S2, the obtained low and medium density graphene powder is molded into blocks to obtain a graphite block with a density greater than or equal to 2g / ml, and then put into a pulverizer for secondary pulverization to obtain a high-density graphene powder; S3. Evenly mix the high-density graphene powder and alumina powder, put them into a vacuum sintering furnace, heat them to high temperature for sintering, and then put them into a pulverizer for three pulverizations after cooling to obtain a composite thermal conductive material.
[0022] The sintering temperature in the vacuum sintering furnace of this embodiment is 500-800° C., and the sintering time is 1-2 hours.
[0023] The composite thermal conductive material of this embodiment is placed in a grinder and fully ground so that the material can pass through a 200-300 mesh screen.
[0024] A preparation process of a high temperature resistant ceramic of this embodiment comprises the following steps: Step 1: grind, wash and remove impurities from the ceramic blank and mix them evenly, then add the composite thermal conductive material and reinforcing fiber and mix them into a slurry for making ceramics, pour the mixed slurry into a mold with microporous holes, let it stand, drain the water by vacuum filtration, and press to obtain a ceramic wet blank; Step 2: Place the formed wet ceramic embryo in a vacuum drying oven for 3-5 hours, and then place it on a wooden rack for air drying, so that the moisture content of the ceramic embryo is controlled at 7-9%, thereby obtaining a dry ceramic embryo; Step 3: Select and remove impurities from the glaze, grind it into powder in a ball mill according to the glaze ratio, then add water, composite thermal conductive material and reinforcing fiber and mix for 1-2 hours, and adjust the glaze concentration to obtain glaze slurry; Step 4: spray the glaze slurry on the surface of the ceramic dry blank, and then put it into a calcining furnace for calcination. The calcination temperature is 1150-1250°C. After calcination for 10-12 hours, keep warm for 3-5 hours. After calcination, cool it to obtain a high-temperature resistant ceramic.
[0025] The ball milling time of the glaze in this embodiment is 20-25 hours, and the fineness after ball milling passes through a 200-250 mesh sieve.
[0026] The present embodiment adopts programmed cooling during cooling, specifically, taking 60 minutes to reduce the temperature to 1000° C., keeping the temperature for 50 minutes, taking another 60 minutes to reduce the temperature to 500° C., keeping the temperature for 30 minutes, and then taking another 40 minutes to reduce the temperature to room temperature. Example 1
[0027] The present invention of this embodiment provides a high temperature resistant ceramic formula, comprising the following raw materials: ceramic blank, glaze, composite thermal conductive material and reinforcing fiber, wherein the composite thermal conductive material and reinforcing fiber are mixed inside the ceramic blank and glaze; The specific formula includes the following raw materials: the mass ratio of the composite thermal conductive material, the reinforcing fiber and the ceramic body is 2:6:100, and the mass ratio of the composite thermal conductive material, the reinforcing fiber and the glaze is 3:7:100.
[0028] The ceramic blank of this embodiment includes the following raw materials: 30 parts of clay, 10 parts of alkaline earth, 15 parts of refractory clay, 3 parts of mullite powder, and 10 parts of titanium oxide; The glaze includes the following raw materials: 15 parts of potassium feldspar, 10 parts of aluminum ore, 10 parts of quartz sand, 12 parts of kaolin, 8 parts of spodumene, 8 parts of calcite, 3 parts of black jade, 12 parts of calcium phosphate, 6 parts of nano titanium dioxide, 8 parts of basic magnesium carbonate, and 2 parts of boric acid.
[0029] The reinforcing fibers of this embodiment include quartz ceramic fibers and silicon carbide ceramic fibers in a ratio of 1:1. The quartz ceramic fibers have a diameter of 3 μm and a length of 0.1 mm, and the silicon carbide ceramic fibers have a diameter of 4 μm and a length of 0.1 mm.
[0030] The preparation method of the composite thermal conductive material of this embodiment comprises the following steps: S1, after natural graphite is rolled, a natural graphite strip with a thickness of 0.5 mm and a density greater than or equal to 1 g / ml is obtained, and then put into a pulverizer for the first pulverization process to obtain medium and low density graphene powder; S2, the obtained low and medium density graphene powder is molded into blocks to obtain a graphite block with a density greater than or equal to 2g / ml, and then put into a pulverizer for secondary pulverization to obtain a high-density graphene powder; S3. Evenly mix the high-density graphene powder and alumina powder, put them into a vacuum sintering furnace, heat them to high temperature for sintering, and then put them into a pulverizer for three pulverizations after cooling to obtain a composite thermal conductive material.
[0031] The sintering temperature in the vacuum sintering furnace of this embodiment is 500° C., and the sintering time is 1 hour.
[0032] The composite thermal conductive material of this embodiment is placed in a grinder and fully ground so that the material can pass through a 200-mesh screen.
[0033] A preparation process of a high temperature resistant ceramic of this embodiment comprises the following steps: Step 1: grind, wash and remove impurities from the ceramic blank and mix them evenly, then add the composite thermal conductive material and reinforcing fiber and mix them into a slurry for making ceramics, pour the mixed slurry into a mold with microporous holes, let it stand, drain the water by vacuum filtration, and press to obtain a ceramic wet blank; Step 2: Place the formed wet ceramic embryo in a vacuum drying oven for 3 hours, and then place it on a wooden rack for airing, so that the moisture content of the ceramic embryo is controlled at 7%, thereby obtaining a dry ceramic embryo; Step 3: Select and remove impurities from the glaze, grind it into powder in a ball mill according to the glaze ratio, then add water, composite thermal conductive material and reinforcing fiber and mix for 1 hour, and adjust the glaze concentration to obtain glaze slurry; Step 4: spray the glaze slurry on the surface of the ceramic dry blank, and then put it into a calcining furnace for calcination. The calcination temperature is 1150°C. After calcination for 10 hours, keep warm for 3 hours. After calcination, cool it to obtain a high-temperature resistant ceramic.
[0034] The ball milling time of the glaze in this embodiment is 20 hours, and the fineness after ball milling exceeds 200 mesh sieve.
[0035] The present embodiment adopts programmed cooling during cooling, specifically, taking 60 minutes to reduce the temperature to 1000° C., keeping the temperature for 50 minutes, taking another 60 minutes to reduce the temperature to 500° C., keeping the temperature for 30 minutes, and then taking another 40 minutes to reduce the temperature to room temperature. Example 2
[0036] The present invention of this embodiment provides a high temperature resistant ceramic formula, comprising the following raw materials: ceramic blank, glaze, composite thermal conductive material and reinforcing fiber, wherein the composite thermal conductive material and reinforcing fiber are mixed inside the ceramic blank and glaze; The specific formula includes the following raw materials: the mass ratio of the composite thermal conductive material, the reinforcing fiber and the ceramic body is 2.5:7:100, and the mass ratio of the composite thermal conductive material, the reinforcing fiber and the glaze is 3.5:8:100.
[0037] The ceramic blank of this embodiment includes the following raw materials: 35 parts of clay, 11 parts of alkaline earth, 16 parts of refractory clay, 4 parts of mullite powder, and 12 parts of titanium oxide; The glaze includes the following raw materials: 18 parts of potassium feldspar, 11 parts of aluminum ore, 11 parts of quartz sand, 13 parts of kaolin, 10 parts of spodumene, 9 parts of calcite, 4 parts of black jade, 14 parts of calcium phosphate, 7 parts of nano titanium dioxide, 9 parts of basic magnesium carbonate, and 3 parts of boric acid.
[0038] The reinforcing fibers of this embodiment include quartz ceramic fibers and silicon carbide ceramic fibers in a ratio of 1:1. The quartz ceramic fibers have a diameter of 6 μm and a length of 0.2 mm, and the silicon carbide ceramic fibers have a diameter of 5 μm and a length of 0.15 mm.
[0039] The preparation method of the composite thermal conductive material of this embodiment comprises the following steps: S1, after natural graphite is rolled, a natural graphite strip with a thickness of 0.8 mm and a density greater than or equal to 1 g / ml is obtained, and then put into a pulverizer for the first pulverization process to obtain medium and low density graphene powder; S2, the obtained low and medium density graphene powder is molded into blocks to obtain a graphite block with a density greater than or equal to 2g / ml, and then put into a pulverizer for secondary pulverization to obtain a high-density graphene powder; S3. Evenly mix the high-density graphene powder and alumina powder, put them into a vacuum sintering furnace, heat them to high temperature for sintering, and then put them into a pulverizer for three pulverizations after cooling to obtain a composite thermal conductive material.
[0040] The sintering temperature in the vacuum sintering furnace of this embodiment is 600° C., and the sintering time is 1.5 h.
[0041] The composite thermal conductive material of this embodiment is placed in a grinder and fully ground so that the material can pass through a 200-300 mesh screen.
[0042] A preparation process of a high temperature resistant ceramic of this embodiment comprises the following steps: Step 1: grind, wash and remove impurities from the ceramic blank and mix them evenly, then add the composite thermal conductive material and reinforcing fiber and mix them into a slurry for making ceramics, pour the mixed slurry into a mold with microporous holes, let it stand, drain the water by vacuum filtration, and press to obtain a ceramic wet blank; Step 2: Place the formed wet ceramic embryo in a vacuum drying oven for 4 hours, and then place it on a wooden rack for air drying, so that the moisture content of the ceramic embryo is controlled at 8%, thereby obtaining a dry ceramic embryo; Step 3: Select and remove impurities from the glaze, grind it into powder in a ball mill according to the glaze ratio, then add water, composite thermal conductive material and reinforcing fiber and mix for 1.5 hours, and adjust the glaze concentration to obtain glaze slurry; Step 4: spray the glaze slurry on the surface of the ceramic dry blank, and then put it into a calcining furnace for calcination. The calcination temperature is 1200°C. After calcination for 111 hours, keep warm for 4 hours. After calcination, cool it to obtain high-temperature resistant ceramics.
[0043] The ball milling time of the glaze in this embodiment is 20-25 hours, and the fineness after ball milling passes through a 200-250 mesh sieve.
[0044] The present embodiment adopts programmed cooling during cooling, specifically, taking 60 minutes to reduce the temperature to 1000° C., keeping the temperature for 50 minutes, taking another 60 minutes to reduce the temperature to 500° C., keeping the temperature for 30 minutes, and then taking another 40 minutes to reduce the temperature to room temperature. Example 3
[0045] The present invention of this embodiment provides a high temperature resistant ceramic formula, comprising the following raw materials: ceramic blank, glaze, composite thermal conductive material and reinforcing fiber, wherein the composite thermal conductive material and reinforcing fiber are mixed inside the ceramic blank and glaze; The specific formula includes the following raw materials: the mass ratio of the composite thermal conductive material, the reinforcing fiber and the ceramic body is 3:8:100, and the mass ratio of the composite thermal conductive material, the reinforcing fiber and the glaze is 4:9:100.
[0046] The ceramic blank of this embodiment includes the following raw materials: 40 parts of clay, 12 parts of alkaline earth, 18 parts of refractory clay, 5 parts of mullite powder, and 13 parts of titanium oxide; The glaze includes the following raw materials: 20 parts of potassium feldspar, 12 parts of aluminum ore, 12 parts of quartz sand, 15 parts of kaolin, 15 parts of spodumene, 10 parts of calcite, 5 parts of black jade, 15 parts of calcium phosphate, 8 parts of nano titanium dioxide, 10 parts of basic magnesium carbonate, and 5 parts of boric acid.
[0047] The reinforcing fibers of this embodiment include quartz ceramic fibers and silicon carbide ceramic fibers in a ratio of 1:1. The quartz ceramic fibers have a diameter of 8 μm and a length of 0.3 mm, and the silicon carbide ceramic fibers have a diameter of 6 μm and a length of 0.2 mm.
[0048] The preparation method of the composite thermal conductive material of this embodiment comprises the following steps: S1, after natural graphite is rolled, a natural graphite strip having a thickness of 1.0 mm and a density greater than or equal to 1 g / ml is obtained, and then the strip is put into a pulverizer for the first pulverization process to obtain medium and low density graphene powder; S2, the obtained low and medium density graphene powder is molded into blocks to obtain a graphite block with a density greater than or equal to 2g / ml, and then put into a pulverizer for secondary pulverization to obtain a high-density graphene powder; S3. Evenly mix the high-density graphene powder and alumina powder, put them into a vacuum sintering furnace, heat them to high temperature for sintering, and then put them into a pulverizer for three pulverizations after cooling to obtain a composite thermal conductive material.
[0049] The sintering temperature in the vacuum sintering furnace of this embodiment is 800° C., and the sintering time is 2 hours.
[0050] The composite thermal conductive material of this embodiment is placed in a grinder and fully ground so that the material can pass through a 300-mesh screen.
[0051] A preparation process of a high temperature resistant ceramic of this embodiment comprises the following steps: Step 1: grind, wash and remove impurities from the ceramic blank and mix them evenly, then add the composite thermal conductive material and reinforcing fiber and mix them into a slurry for making ceramics, pour the mixed slurry into a mold with microporous holes, let it stand, drain the water by vacuum filtration, and press to obtain a ceramic wet blank; Step 2: Place the formed wet ceramic embryo in a vacuum drying oven for 5 hours, and then place it on a wooden rack for airing, so that the moisture content of the ceramic embryo is controlled at 9%, thereby obtaining a dry ceramic embryo; Step 3: Select and remove impurities from the glaze, grind it into powder in a ball mill according to the glaze ratio, then add water, composite thermal conductive material and reinforcing fiber and mix for 2 hours, and adjust the glaze concentration to obtain glaze slurry; Step 4: spray the glaze slurry on the surface of the ceramic dry blank, and then put it into a calcining furnace for calcination. The calcination temperature is 1250°C. After calcination for 12 hours, keep warm for 5 hours. After calcination, cool it to obtain high-temperature resistant ceramics.
[0052] The ball milling time of the glaze in this embodiment is 25 hours, and the fineness after ball milling is beyond 250 mesh sieve.
[0053] The present embodiment adopts programmed cooling during cooling, specifically, taking 60 minutes to reduce the temperature to 1000° C., keeping the temperature for 50 minutes, taking another 60 minutes to reduce the temperature to 500° C., keeping the temperature for 30 minutes, and then taking another 40 minutes to reduce the temperature to room temperature.
[0054] Comparative Example 1. The difference from Example 3 is that a common formula is used to prepare high temperature resistant ceramics.
[0055] Comparative Example 2. The difference from Example 3 is that only composite thermal conductive material is added to prepare high temperature resistant ceramics.
[0056] Comparative Example 3. The difference from Example 3 is that only reinforcing fibers are added to prepare high temperature resistant ceramics.
[0057] The products of Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests; 300 high temperature resistant ceramic samples were prepared and divided into 6 groups with 50 samples in each group. Each group corresponded to Examples 1-3 and Comparative Examples 1-3 and were numbered A / B / C / D / E / F. Finally, the high temperature resistant ceramic samples of groups A / B / C / D / E / F were tested respectively. The test results are shown in the following table.
[0058]
[0059] It can be seen from Examples 1-3 that the high-temperature resistant ceramic formula and preparation process made using the present invention, by strictly controlling the proportion of each component of the ceramic blank and glaze and the preparation process parameters, and adding reinforcing fibers and composite thermal conductive materials to the ceramic blank and glaze, the ceramic has better wear resistance and high temperature resistance.
[0060] As can be seen from Example 3 and Comparative Example 2, the composite thermal conductive material is added, wherein the graphite powder and alumina powder can be evenly distributed in the ceramic blank and glaze, and form a network structure with the reinforcing fiber. The thermal conductivity of the graphite powder greatly improves the thermal conductivity of the ceramic material, effectively disperses the load, disperses the stress, and prevents crack propagation; It can be seen from Example 3 and Comparative Example 3 that by adding reinforcing fibers to the ceramic blank and glaze, because they are thin and soft, they will naturally bend during stirring and molding, which does not affect the use, and plays a role in increasing the strength of the ceramic and reducing cracks.
[0061] The innovation of the present invention is: The present invention strictly controls the proportion of each component of the ceramic blank and glaze and the preparation process parameters, and adds reinforcing fibers to the ceramic blank and glaze. Because the reinforcing fibers are thin and soft, they will naturally bend during stirring and molding, which does not affect the use, thereby increasing the strength of the ceramic and reducing cracks. At the same time, a composite thermal conductive material is added, wherein the graphite powder and alumina powder can be evenly distributed in the ceramic blank and glaze, and form a network structure with the reinforcing fibers. The thermal conductivity of the graphite powder greatly improves the thermal conductivity of the ceramic material, effectively disperses the load, disperses the stress, and prevents the crack from expanding. At the same time, the alumina powder, because of its relatively small particles, large surface area, and good activity, can promote the burning of the material, so that the ceramic has better wear resistance and high temperature resistance.
[0062] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0063] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high temperature resistant ceramic formula, characterized in that: The method comprises the following raw materials: a ceramic blank, a glaze, a composite heat-conducting material and reinforcing fibers, wherein the composite heat-conducting material and the reinforcing fibers are mixed inside the ceramic blank and the glaze; Its specific formula The invention comprises the following raw materials: the mass ratio of the composite thermal conductive material, the reinforcing fiber and the ceramic body is (2-3): (6-8): 100; the mass ratio of the composite thermal conductive material, the reinforcing fiber and the glaze is (3-4): (7-9):
100.
2. A high temperature resistant ceramic formula according to claim 1, characterized in that: Including the following ingredients: The mass ratio of the composite thermal conductive material, the reinforcing fiber and the ceramic body is 2.5:7:100, and the mass ratio of the composite thermal conductive material, the reinforcing fiber and the glaze is 3.5:8:
100.
3. A high temperature resistant ceramic formula according to claim 1, characterized in that: The ceramic blank comprises the following raw materials: 30-40 parts of clay, 10-12 parts of alkaline earth, 15-18 parts of refractory clay, 3-5 parts of mullite powder, and 10-13 parts of titanium oxide; The glaze comprises the following raw materials: 15-20 parts of potassium feldspar, 10-12 parts of aluminum ore, 10-12 parts of quartz sand, 12-15 parts of kaolin, 8-15 parts of spodumene, 8-10 parts of calcite, 3-5 parts of black jade, 12-15 parts of calcium phosphate, 6-8 parts of nano titanium dioxide, 8-10 parts of basic magnesium carbonate and 2-5 parts of boric acid.
4. A high temperature resistant ceramic formula according to claim 3, characterized in that: The reinforcing fibers include quartz ceramic fibers and silicon carbide ceramic fibers in a 1:1 ratio. The quartz ceramic fibers have a diameter of 3-8 μm and a length of 0.1-0.3 mm. The silicon carbide ceramic fibers have a diameter of 4-6 μm and a length of 0.1-0.2 mm.
5. A high temperature resistant ceramic formula according to claim 4, characterized in that: The preparation method of the composite thermal conductive material comprises the following steps: S1, after natural graphite is rolled, a natural graphite strip with a thickness of 0.5-1.0 mm and a density greater than or equal to 1 g / ml is obtained, and then put into a pulverizer for the first pulverization process to obtain medium and low density graphene powder; S2, the obtained low and medium density graphene powder is molded into blocks to obtain a graphite block with a density greater than or equal to 2g / ml, and then put into a pulverizer for secondary pulverization to obtain a high-density graphene powder; S3. Evenly mix the high-density graphene powder and alumina powder, put them into a vacuum sintering furnace, heat them to high temperature for sintering, and then put them into a pulverizer for three pulverizations after cooling to obtain a composite thermal conductive material.
6. A high temperature resistant ceramic formula according to claim 5, characterized in that: The sintering temperature in the vacuum sintering furnace is 500-800° C., and the sintering time is 1-2 hours.
7. A high temperature resistant ceramic formula according to claim 5, characterized in that: The composite thermal conductive material is placed in a grinder and fully ground so that the material can pass through a 200-300 mesh screen.
8. A process for preparing the high temperature resistant ceramic according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: grind, wash and remove impurities from the ceramic blank and mix them evenly, then add the composite thermal conductive material and reinforcing fiber and mix them into a slurry for making ceramics, pour the mixed slurry into a mold with microporous holes, let it stand, drain the water by vacuum filtration, and press to obtain a ceramic wet blank; Step 2: Place the formed wet ceramic embryo in a vacuum drying oven for 3-5 hours, and then place it on a wooden rack for air drying, so that the moisture content of the ceramic embryo is controlled at 7-9%, thereby obtaining a dry ceramic embryo; Step 3: Select and remove impurities from the glaze, grind it into powder in a ball mill according to the glaze ratio, then add water, composite thermal conductive material and reinforcing fiber and mix for 1-2 hours, and adjust the glaze concentration to obtain glaze slurry; Step 4: spray the glaze slurry on the surface of the ceramic dry blank, and then put it into a calcining furnace for calcination. The calcination temperature is 1150-1250°C. After calcination for 10-12 hours, keep warm for 3-5 hours. After calcination, cool it to obtain a high-temperature resistant ceramic.
9. A process for preparing high temperature resistant ceramics according to claim 8, characterized in that: The ball milling time of the glaze is 20-25 hours, and the fineness after ball milling is through a 200-250 mesh sieve.
10. The process for preparing high temperature resistant ceramics according to claim 8, characterized in that: The cooling is performed by programmed cooling, specifically, cooling to 1000° C. in 60 minutes, keeping the temperature for 50 minutes, cooling to 500° C. in 60 minutes, keeping the temperature for 30 minutes, and cooling to room temperature in 40 minutes.
Citation Information
Patent Citations
High-temperature-resistant ceramic composite material as well as preparation method and application thereof
CN113045301A
High-temperature-resistant ceramic composite material as well as preparation method and application thereof
CN113087505A
Cited By
Dehua white porcelain sculpture preparation process based on natural loofah sponge fiber reinforcement
CN119977523A
Special coating for large machine tool casting lost foam as well as application and use method of special coating
CN121467614A
A special coating for large machine tool casting lost foam and its application and use method
CN121467614B